PERTUMBUHAN UMAT KATOLIK DI ASIA TENGGARA BERDASARKAN KONTEN YOUTUBE @KATOLIK_KEREN - Bayu Lesmana, Iknasius; Boromeus Mulyatno, Carolus; Antony, Rian (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
Church development can be defined into two, namely quantitative and qualitative growth. Not all people know about the development of Catholics internationally, including history, pastoral officials, people's habits, and the state of the Church. The YouTube channel @katolikku_keren is a Catholic account that can be used to examine the development of Catholics in Southeast Asia. This research uses the YouTube content analysis method @katolikku_keren. The author will observe the content of several videos on the YouTube channel @katolikku_keren and implement it with Church growth strategy theory. The results of this research are that since the 16th century, Catholics began to develop in Southeast Asia. The people who supported this development were the first missionaries, congregational priests, diocesan priests, brothers, sisters and the faithful. Meanwhile, the universal vision is for Catholics to develop dialogue between religions, education, health and orphanages. The YouTube channel @katolikku_keren tries to show the face of the Church internationally.